The Influence of Organizational Citizenship Behavior on The Performance of Teachers in Elementary School - Fauziah, Siti; Hali, Ali Usman; Jaya, Abdul Rahman (Munaddhomah: Jurnal Manajemen Pendidikan Islam, 2025)
. Extra-work behavior plays a crucial role in achieving organizational goals in educational institutions. This study examines the impact of organizational citizenship behavior (OCB) on teacher performance at Madrasah Ibtidaiyah Asy-Syafi'iyah Kendari City. Using a quantitative research approach, the study utilized both primary and secondary data sources. Data were collected through survey techniques by distributing questionnaires to 34 teachers. The research variables were measured using appropriate scales, and the collected data were analyzed through linear regression analysis. The findings indicate that OCB has a positive and significant effect on teacher performance. The correlation coefficient results further confirm that OCB significantly influences performance, suggesting that teachers who exhibit high levels of extra-role behavior contribute more effectively to their institutions. Despite these contributions, this study has several limitations. First, the small sample size of 34 teachers may not fully represent the broader population, limiting the generalizability of the findings. Second, the study relies solely on self-reported data, which may introduce response bias. Third, the use of a cross-sectional design prevents the identification of long-term causal effects between OCB and teacher performance. Future research should consider a larger sample, multiple data sources, and a longitudinal approach to provide a more comprehensive understanding of OCB’s impact on teacher performance.